Metastatic myxosarcoma in a Quarter Horse gelding. (January 2018) - Samuelson, Jonathan P.; Echeverria, Kate O.; Foreman, Jonathan H.; Fredrickson, Richard L.; Sauberli, Deborah; Whiteley, Herbert E.
A 22-y-old Quarter Horse gelding was presented to the University of Illinois Veterinary Teaching Hospital for evaluation of increased heart rate and mild colic signs. Rectal examination revealed a large left perirenal mass. Abdominal ultrasonography further confirmed this finding. Thoracic ultrasonography indicated multifocal irregularities on the pleural surface suggestive of consolidation and possibly masses in the lungs. The animal was euthanized. Autopsy findings included a large, firm, expansile, gelatinous retroperitoneal mass that surrounded both kidneys, as well as nodules with similar morphology in the lungs, liver, intestinal mesentery, cecum, and caudal mesenteric artery. Histologically, the masses were composed of neoplastic stellate-to-spindloid cells in abundant mucinous stroma. Neoplastic cells exhibited strong immunoreactivity for vimentin and were negative for pancytokeratin (A1/A3), CD3, CD20, melan A, and synaptophysin. Mucinous stroma was strongly positive with alcian blue and weakly positive with periodic acid–Schiff histochemical staining. These findings are consistent with metastatic myxosarcoma. Myxosarcoma is a rare neoplasm in horses, and metastasis to tissues other than sentinel lymph nodes has not been described previously to our knowledge.